(b + 4)(b + 4)
3b+4 = b+12 3b-b = 12-4 2b = 8 b = 4
(b + 8)(b + 4)
b + 4 = 7.7 b = 7.7 - 4 b = 3.7
The expression "b plus b plus b plus b" can be simplified by combining like terms. Since all the terms are the same (b), we can add them together. Adding b four times is the same as multiplying b by 4. Therefore, "b plus b plus b plus b" equals 4b.
(a + 2 - b) (a + 2 + b)
(b+8)(b+4)
= a + b - 2
13b+6c
(b + 8)(b + 4)
Symmetry, which states that if A = B then B = A Put A = 4 and B = x + y
(b + 2)(b + 2) or (b + 2)2